EZH2 mutations and impact on clinical outcome: an analysis in 1,604 patients with newly diagnosed acute myeloid leukemia - Stasik, Sebastian; Krämer, Alwin; Müller-Tidow, Carsten (Haematologica, 2020)
The enhancer of zeste homolog 2 (EZH2) is a histone methyltransferase and functional core subunit of the polycomb repressive complex 2 (PRC2), which is a key epigenetic regulator involved in embryonic development and transcriptional repression of genes by catalyzing the methylation of histone H3 at